Preliminary effect of projectile yaw on extremity gunshot wounding in a cadaveric animal model: a serendipitous study - Stevenson, Tom; Carr, Debra J.; Gibb, Iain E.; Stapley, Sarah A. (Springer, 2020)
Gunshot wounding (GSW) is capable of causing devastating tissue injuries by delivering kinetic energy (KE) through the contact surface area of a projectile. The contact surface area can be increased by yaw, deformation and fragmentation, all of which may be caused by any intermediate layers struck by the projectile prior to entering its target. This study aims to describe whether projectile yaw occurring before penetration of a cadaveric animal limb model causes greater damage with or without clothing layers present using 5.45 × 39 mm projectiles. In total, 12 fallow deer hind limbs were shot, further divided into 4 with no clothing layers (Cnil), 4 with a single clothing layer (Cmin) and 4 with maximum clothing layers (Cmax) as worn on active duty by UK military personnel. Contrast computed tomography (CT) of limbs was used to measure permanent cavity size and the results were compared using analysis of variance (ANOVA). No significant differences were found among clothing states for each series of measurements taken, with greater cavity sizes noted in all clothing states. This is in contrast to previous work looking at symmetrically flying projectiles in the same model, where a larger permanent cavity was found only with Cmax present. Projectile yaw is therefore likely to be a key variable with regard to causation of damage within this extremity wound model.
Keywords: Yaw; Gunshot; Wounding; Clothing; Extremity; AK74